SUSTAINABLE GLOBAL BEST PRACTICES AND NIGERIA TOURISM ECONOMY: IMPLICATION FOR THE INDUSTRYS’ ENHANCED PERFORMANCE AND GROWTH - Yekinni Ojo Bello; Ofodu Amelia Jennifer; Mercy Busayo Bello (Scholars Digest Publishing, 2025)
The paper proposes Sustainable Global Best Practices and Tourism Economy Performance and growth model to explain the connection between the two constructs in respect of Nigeria. The study adopted a literature review approach to present a hypothetical model of Sustainable Global Best Practices as an independent variable with six dimensions (i.e. Sustainable tourism / hospitality business infrastructure, sustainable security architecture, sustainable AI and technology adoption, sustainable tourism / hospitality business policy, sustainable data gathering and data management, and tourism resources profiling and tourism / hospitality product development) that influences Tourism Economy Performance and growth in Nigeria. The argument in this study opines that Sustainable Global Best Practices has the capability of enhancing the realisation of Tourism Economy Performance and growth in Nigeria if given due attention. The model is useful for analysis in academic and tourism business research, including impact studies. The framework has potential application in sustainable tourism development in respect of Nigeria. It can as well serve as a guide for tourist mobility planning and assessing government policies on tourism development issues. The limitations of this study stem from the nature of the study itself. As a theoretical model, it aims to integrate the goals identified in the existing literature. Thus, future research must try to examine the existing relationships among the aforementioned factors. In particular, it must analyse the weight of each goal and the relative importance of each for the factor it belongs to. Since there are few studies that reported the association between tourism and sustainable development goals in Nigeria from an integrated point of view, this paper contributes to bridging this gap. Thus, contributing to tourism and sustainable development goals literature in an emerging economy.
Keywords: Tourist arrival, Tourist receipts, Sustainable global best practices; Tourism economy performance; Tourism economy growth.